SIMULATION AND MODELING THE DEFERRED BEHAVIOR INDUCED BY THE CREEP OF A REINFORCED CONCRETE SECTION - C. Oubraham; S. Drizi; B. Safi; A. Benmounah (European Scientific Journal, ESJ, 2013)
﻿In the reinforced concrete structures, the differed deformations due to creep increase with time. They become dominating compared to the instantaneous strains, corresponding to a given loading. In order to ensure itself of the good behavior of an element or a concrete structure reinforced in service and with the absolute limit, it is necessary to correctly evaluate the instantaneous and differed deformations and displacements. Within the framework of this study one is interested in modeling and simulation of the behaviors instantaneous and differed from a zone bent out of reinforced concrete. For the simulation of the instantaneous behavior, in composed inflection, an existing program is used and of the complements of validations is realized. For the modeling of the differed behavior, a formulation based on the method of the adjusted effective module is presented. Another data-processing program is developed. It makes it possible to simulate the deformations of a zone bent under loading supported in time. The differed effects are taken into account by using the coefficient of creep recommended by the CEB 90. The simulations carried out on experimental tests allow the validation of the approach used. The results show that the best functioning of the approach used by the program and the comparison test-calculation is satisfactory.